Income support policies for part-time workers: a stepping-stone to regular jobs? ; An application to young long-term unemployed women in Belgium - Bart Leo Wim Cockx; Stéphane Robin; Christian Goebel (Institute for the Study of Labor (IZA), 2006)
We verify whether an income support policy for part-time workers in Belgium increases the transition from unemployment to non-subsidised, regular employment. Using a sample of 8630 long-term unemployed young women, whose labour market history is observed from 1998 to 2001, we implement the timing of events approach proposed by Abbring and Van den Berg (2003) to control for selection effects. Our results suggest that the policy has a significantly positive effect on the transition to non-subsidised employment when one does not control for unobserved heterogeneity. This effect remains positive, but becomes insignificant, when one corrects for selection on unobservable characteristics.
urn:nbn:de:101:1-2008072465
Keywords: 330; Frauenarbeitslosigkeit; Langzeitarbeitslosigkeit; Lohnsubvention; Beschäftigungseffekt; Teilzeitarbeit; Schätzung; Belgien